Von Chancen und Statuskämpfen: Klassenverhältnisse in der Erziehungsgesellschaft - Draheim, Susanne; Krause, Alexandra; Reitz, Tilman (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2010)
The authors explore how education policies of increased individual and institutional competition affect class relations. They assume that especially the middle classes, whose strategies of social closure and social mobility are mainly based on education, react with intensified and extended private educational investments. Contrary to what the dominant political discourse suggests, this dynamic would even reinforce existing class boundaries. To substantiate their assumption, the authors analyse recent changes in the educational institutions and the employment system. Moreover, they study recent social and discursive conflicts on educational reforms and their legitimacy.